Between Nobel and Confucius - Razak, Dzulkifli Abd (2011)
THE recent Nobel Peace Prize award ceremony came and went without much of the usual fanfare. The publicity it garnered was rather mellow, ranging from reports of boycotts, threats and accusation of bias to disrespect.